Lost in translation in university teaching: emphasis on teaching the emphasis on learning - Altair Alberto Fávero; Deloíze Lorenzet (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The convulsions that shook the world in recent times could not fail to affect college life also. The expansion of higher education took place in the past two decades reascende the debate of old and new challenges: what is expected of higher education in this new scenario? What are the grounds that boosted this expansion? Internal and external elements are acting in this context? How are you restructuring higher education to meet the new demands that are emerging? How is being thought about the teaching and learning process of the large contingent of students who come to higher education? The proposed article aims analyze the "dates" and "misunderstandings" that emerge in university teaching in the light of the research which has problematized the educational practices in educational institutions. In order to delimit the subject of research, the authors chose to examine University teaching from two paradigms: the paradigm that emphasizes education and the emphasis on learning paradigm. The authors advocate the position that any teaching practice from behind a paradigm that needs to be made explicit, analyzed and discussed so that the educational process is a conscious act and may suffer its improvement promoting interventions. Not identifying the paradigm that guides the teaching practice can result in the activation of dumbfounding attitudes that transform teaching in a mechanical action and instrumental. Starting from a contextualization of the reasons which led to the expansion of higher education and of the consequences that such expansion brought to the identity, the authors perform a characterization of two possible paradigms that pertain to university teaching and the consequences of such paradigmatic option has on academic training.